Urgency Of Project Based Learning Model In Social Studies Learning To Improve Students Learning Achievement - Siti Samsiyah; Akhmad Arif Musadad; Musa Pelu (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to describe the importance of a project based learning model in social studies learning to improve student achievement. This research is a descriptive qualitative study with a naturalistic approach. This research was conducted at SMP IT MTA Karanganyar. Data collection was carried out through in-depth interviews, observation and document analysis. The research instrument is the author himself as a data collector. The data validation was done by using triangulation techniques, double checking, and peer question and answer. Data analysis was performed using interactive analysis techniques which included data collection, data reduction, data display, and verification of conclusion. From the research results it can be concluded that the project based learning model is very important in social studies learning to improve student achievement. The increase in student learning achievement can be seen in the increase in student learning outcomes in material relics of the Hindu and Buddhist kingdoms in Indonesia. Project Based Learning assists teachers in developing student skills in making products that have benefits for students in participating in classroom learning. This condition is the main asset used in implementing the 2013 curriculum to create a generation that is superior, intelligent, creative, has quranic morals and environmentally friendly characters.